1 / 7

# An example: - PowerPoint PPT Presentation

An example: Taking the example discussed above of force F induced on a propeller blade, we have the equation 0 = φ (K, d, u, ρ , N, μ ) There are m - n = 3 π groups, so φ ( π 1 , π 2 , π 3 ) = 0

I am the owner, or an agent authorized to act on behalf of the owner, of the copyrighted work described.

## PowerPoint Slideshow about ' An example:' - donkor

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript

• An example:

Taking the example discussed above of force F induced on a propeller blade, we have the equation

0 = φ (K, d, u, ρ, N, μ)

There are m - n = 3 π groups, so

φ( π1 , π2 , π3 ) = 0

• The choice of ρ, u, d as the repeating variables satisfies the criteria above. They are measurable, good

design parameters and, in combination, contain all the dimension M,L and T. We can now form the three

groups according to the 2nd theorem,

As the πgroups are all dimensionless i.e. they have dimensions M0L0T0 we can use the principle of

dimensional homogeneity to equate the dimensions for each πgroup.

For the first π group, in terms of dimensions

M0L0T0 = (ML-3)a1 (LT-1)b1 (L)c1 MLT-2

For each dimension (M, L or T) the powers must be equal on both sides of the equation, so

For M: 0 = a1 + 1

a1 = -1

For L: 0 = -3a1 + b1 + c1 +1

0 = 4 + b1 + c1

For T: 0 = -b1 – 2

b1 = -2

c1 = -4 – b1 = -2

Giving π1 as

For π2 we have,

M0L0T0 = (ML-3)a2 (LT-1)b2 (L)c2 T-1

For M: 0 =a2

a2 = 0

For L: 0 = -3a2 – b2 + c2

0 = - b2 + c2

For T: 0 = -b2 – 1

b2 = -1

c2 = 1

Giving π2 as

For π3 we have

M0L0T0 = (ML-3)a3 (LT-1)b3 (L)c3 ML-1T—1

For M: 0 = a3 + 1

a3 = -1

For L: 0 = -3a3 + b3 + c3 -1

0 = b3 + c3 +2

For T: 0 = -b3 -1

b3 = -1

c3 = -1

Giving π3 as